EFEKTIFITAS PRODUKSI TELUR ASIN KUM âANGGREKâ DENGAN TEKNOLOGI TEPAT GUNA - Bahri, Syamsul; Hasan, Khojanah (DINAMIKA DOTCOM, 2017)
Salted egg products are commercials product that have prospect, it was proved by the huge number of demand, also we can see that the turnover is increasing from year to year. Salted egg products have the nutrients that meet the criteria as a high biological valuable food because the protein is easily digested by the digestibility coefficient of of 96%, it has a good taste and has so many benefits for children under five (requires 15 grams of protein per day), pregnant women, breastfeeding mother, also for elderly. Proposes Village area PurwoasriSingosari Malang regency as a research location, because in that area there is a group of Independent Business of Anggrek which are very active and enthusiastic in this entrepreneurship program, so it can be used by local people as a means to augment the womens activities and also to earn additional income. The initial goal of these cooperation is to empower local residents and the wider community to create jobs, therefore the need for guidance in this business development terms. Problems that occured among the others are in the process of making salted eggs there are 2 times washing stages, which are washing prior to wrap the dough and washing after immersion in the dough. The process has been done by washed eggs one by one manually, thereby it will inhibit the production process and take a long time. In addition to the limitations of management planning and lack of proper accounting,Â lack of marketing techniques and has not been able to calculate the exact cost of production lead them to the result of inaccurate in pricing. Proposer chose this salted egg production on several considerations, which are: market absorption is still very high and potential considerable, the needs of expertise (skills) that are not so high and low cost investment. The method of implementation that will be used is to design the eggs cleanup tool and provide education, training and mentoring of management, marketing, accounting and information systems with a simple bookkeeping (the Financial Statements).Â Â Â Â Â Keyword : Independent Business, Salted Egg